Pengaruh Literasi Keuangan, Financial Technology, dan Gaya Hidup terhadap Perilaku Keuangan Guru Taman Kanak-Kanak - M Iqbal Zarkasyi; Eko Purwanto (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The current teaching profession is very promising in terms of income, especially for those who have obtained a professional diploma. The government provides additional income or allowances for public and private teachers through a teacher qualification certification program. The government is trying to improve the professionalism of teachers, but in reality, there are not a few teachers who view from the wrong point of view that the professional allowance is a teacher's right and a government obligation. The purpose of this study was to determine the effect of financial literacy, financial technology, and lifestyle on financial behavior in kindergarten teachers in the Sukolilo District, Surabaya City. Determination of the sample using the slovin method with purposive sampling technique resulted in a total sample of 74 respondents. The data analysis technique used is Partial square (PLS). The results of this study indicate that financial literacy has a positive and significant effect on financial behavior, financial technology is not significant to financial behavior, and lifestyle has a positive and significant effect on financial behavior.